Developmental changes in human fetal kidney - M Jayasabarinathan; S Vijayadevi (National Journal of Clinical Anatomy, 2018)
Aims and objectives: It is necessary to know the normal developmental Anatomy of the kidney to understand certain prenatal disorders like polysystic kidney, hydronephrosis and Wilm's tumour. A detailed description of histological development of kidney is scarce. Therefore the present study is an attempt to further the anatomical knowledge in histogenesis of kidney. Materials & Method: The study was carried out in the department of Anatomy, Mount Zion Medical College, Adoor, Kerala. 30 dead born fetuses (gestational age range from 11 weeks to 3 6 weeks) were utilized for the study. Tissue specimen from the kidneys were stained with Hematoxylin and Eosin and examined under light microscope. Results: Nephrogenic zone was identified up to 34 wks of gestation. Cortex was clearly distinguished from medulla at 14 th wk of fertilization. Different shapes [S & C] of glomeruli were identified in the second trimester. At 24 th wk, proximal convoluted tubule [PCT], distal convoluted tubule [DCT], collecting duct and thin and thick segment of loop of Henle were identified clearly. Conclusion: The pathological conditions of the kidney can be diagnosed at the earliest by understanding the normal histological development of the kidney at various stages. This study would be helpful for understanding the normal histological development of kidney.